2009
DOI: 10.1007/s11467-009-0055-l
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced vacuum Rabi splitting and double dark states in a composite atom-cavity system

Abstract: The transmission spectrum of four-level atoms in a cavity is calculated. It is shown that the four separate peaks associated with normal mode splitting and intra-cavity double dark states can be observed simultaneously. The position and intensity of the four peaks can be controlled by the intensity of the third interacting light. Therefore, the enhancement of normal mode splitting by a third coupling light of the intra-cavity four-level atoms is developed.Normal mode splitting (also called vacuum Rabi splittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It can be found that the frequency interval of VRS becomes larger as coupling laser power increases [23]. The relationship between the VRS interval (Δ VRS ) and coupling laser Rabi frequency (Ω c ) is [33]. The amplitude and FWHM of the transmission peak of 5S 1/2 -56D 5/2 transition also gradually increase, and the corresponding amplitude (squares) and FWHM (dots) are extracted from the inset of Figure 4.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It can be found that the frequency interval of VRS becomes larger as coupling laser power increases [23]. The relationship between the VRS interval (Δ VRS ) and coupling laser Rabi frequency (Ω c ) is [33]. The amplitude and FWHM of the transmission peak of 5S 1/2 -56D 5/2 transition also gradually increase, and the corresponding amplitude (squares) and FWHM (dots) are extracted from the inset of Figure 4.…”
Section: Resultsmentioning
confidence: 96%
“…It can be seen that the VRS interval increases as atomic density increases, which is precisely controlled by changing the temperature of vapor. The VRS interval (Δ VRS ) can be expressed as Δ VRS = 2 g 2 N + Ω 2 c /4 [25,33], where Ω c is the Rabi frequency of coupling laser. However, the probe laser is vigorously absorbed for the VRS process as the atomic density increases, which results in the corresponding decrease of CAEIT amplitude.…”
Section: Resultsmentioning
confidence: 99%